ANALYSIS OF FACTORS INFLUENCING THE INTEREST OF FOREIGN TOURISTS TO REVISIT BALI - Widanta, Agung (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 1, Februari 2021 (pp.1-241)DO - 10.24843/JEKT.2021.v14.i01.p10, 2021)
Bali Province is not endowed with natural resources to drive its economy, but rather relies heavily on tourism as its leading sector in achieving economic growth. Against the backdrop of Bali's heavy dependence on tourism, it is necessary to conduct an analysis on how to survive the fierce tourism competition. There are mainly four strategies for attracting investments, tourists and industries into a region, namely: image, which is a set of beliefs, ideas and expressions that a person has towards a region; attraction marketing, which is attraction of a tourist destination; infrastructure marketing, which is the availability of facilities and infrastructures that can attract people, investments and capital; and people marketing, which is a strategy to market a region by marketing the attitudes of its people: how open the local community is to foreign influences (people, investments, industries and products). This study finds that image, infrastructure marketing, attraction marketing and people marketing have positive and significant effects on the interest of foreign tourists to revisit Bali. The results of this study provide a comprehensive picture for the government and related parties in formulating tour packages to attract foreign tourists to revisit Bali.